People of Anatolia past, current and future research in the biological anthropology of Türkiye - Irvine, Benjamin Titus; Erdal, Yılmaz Selim 19XX-; Vandeput, Lutgarde ca. 20./21. Jh (British Institute at Ankara, 2024)
People of Anatolia: Past, Current and Future Research in the Biological Anthropology of Türkiye brings together, in one complete volume, some of the current research foci and trends of biological anthropology in Türkiye. The papers within this edited volume cover a multitude of topics, many of which complement and enhance each other, helping to demonstrate the strength and variety of research currently being performed in Türkiye by both domestic and foreign researchers. Furthermore, several of these papers examine large scale diachronic changes and highlight the importance of such holistic approaches and methodological considerations, and new trends in modern research by considering large scale patterns through time and space and the ?bigger? picture. For example, the application of multiple, more traditional macroscopic, biological anthropological analyses in conjunction with more modern techniques, such as biomolecular analyses.0Biological anthropology in Türkiye has developed markedly since the days of primarily analyzing skeletal and dental morphometrics of the skeleton and investigating race. This is particularly true since the 1990s when studies have examined skeletal remains from Anatolia within wider bioarchaeological contexts and research questions. Research agendas have accelerated particularly in the last decade with the introduction and application of new methodologies, including quantifiable scientific techniques which has increased the ability to not only tackle existing and earlier research questions with more specificity and in more depth, but also enables us to tackle a greater variety of research questions, as well as stimulating new ones
"Inspired by the workshop 'Physical anthropology in Anatolia', which was held at the British Institute at Ankara (BIAA) on the 8th of November 2019"--page 3
Keywords: Human remains (Archaeology) / Turkey / Congresses; Turkey / Population / History / To 1500 / Congresses; Asia Minor; Konferenzschrift -- 2019 -- Ankara; Aufsatzsammlung